Sampling techniques for and interpretation of milk urea nitrogen concentration - A.F. Park; John F. Smith; Timothy G. Rozell; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1998)
Representative MUN values can be obtained by testing a milk sample before milking, at AM or PM milking, or with an in-line siphon sampling device. MUN values obtained from homogenous milking strings are as accurate as an average MUN value obtained by sampling each cow in the string. Bulk tank sampling is not advisable because of the variation in MUN caused by stage of lactation. Small herds that feed a single TMR should use the average MUN from cows between 60 and 200 days in milk. Monthly sampling is recommended to build a database. The effect of diet changes on MUN can be assessed within 7 days.; Dairy Day, 1998, Kansas State University, Manhattan, KS, 1998;
Keywords: Dairy Day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-158-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 821; Milk sampling; Milk urea nitrogen; Blood urea nitrogen